Determinants of employee engagement among employees in Rubber Industry Smallholder Development Authority (RISDA) Kuala Lumpur / Nurul Ain Othman - Othman, Nurul Ain (Faculty of Business and Management, 2018)
Employee engagement has been one of the crucial issues faced by the employer in the country. When there is high involvement of the employee in the organization, it will lead to produce an excellent performance in their job. Therefore, this study aims to investigate the determinants of engagement among employees in RISDA KL. This research was aimed to achieve the following objectives; examine the relationship between work environment and employee engagement in RISDA KL; identify how leadership roles give impact on employee engagement at RISDA; determine how team and co-worker can affect employee engagement in RISDA; and investigate whether training and development give impact on employee engagement in RISDA. The total population of the research is 738 employees of RISDA KL with sample size of 186 respondents. Convenience sampling has been used as sampling technique for this research. In addition, Likert scale was used to collect data from respondent. The questionnaire had Cronbach alpha of α= 0.904 which above the instrument is reliable. Furthermore, the results shown that leadership role and training and development have a positive and significant relationship towards employee engagement. However, for working environment and team and co-worker relationship are not significant to the employee engagement. Therefore, the results will help the organization to increase the level of employee engagement in order to achieve the targets of the organization.